ORGANIZATION OF BUDGET MANAGEMENT IN THE PROJECTS OF CONSTRUCTION AND REPAIR OF CARGO SHIPS - Антикова, Ирина Валерьевна; Фатеев, Николай Владимирович; Запорожец, Ирина Михайловна (Eastern-European Journal of Enterprise Technologies, 2013)
Budgeting is an effective project management technology that allows to improve the quality of operational management and achieve strategic objectives. The purpose of the paper is to develop mechanisms for building organizational procedures governing relations among departments in dockyard budget management system. Significant duration of construction and repair of ships, as well as a high degree of uncertainty make it necessary to support three interrelated systems of budgets: 1) the basic budget is formed in the planning stages of income and expenses for each project; 2) the current project budgets show the results of regulatory impacts, i.e., record all changes of planned parameters; 3) the actual project budgets are formed at the end of work and are final document at the conclusion of the project. To develop network models, project construction and repair of ships at the enterprise it is necessary to organize project management office authorized: a) to develop of basic project and operating budgets to support the implementation of the results of the control actions; b) to coordinate of communication management among various projects; c) to centralize monitoring of all budgets to ensure the integrity and consistency of all elements of the budget system of the enterprise; d) to optimize of the use of shared resources of the enterprise; e) to provide project managers with traffic information resources and all the leaders of the centers of financial responsibility in the terms established by the budget rules.